2022
DOI: 10.1029/2022jb024216
|View full text |Cite
|
Sign up to set email alerts
|

GPS Determined Asymmetric Deformation Across Central Altyn Tagh Fault Reveals Rheological Structure of Northern Tibet

Abstract: We establish a continuous GPS transect crossing the central Altyn Tagh fault at 90°E with eight years of observations. GPS velocities along this profile and another one crossing the fault at 86°E suggest a fault slip rate of 12.4 ± 0.7 mm/yr, but with asymmetric straining of adjacent terrain. On the south side, ∼8.2 mm/yr of left‐lateral shear is absorbed across a region ∼210 km from the fault, but only ∼4.2 mm/yr is found on the north side. This estimate of slip rate is ∼30% larger than the consensus estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…The 3D velocity field from joint inversion is shown in Figure 3 (Ge, 2023; Figures 3a–3c, Figure S2a–S2c in Supporting Information ). We compare the mean velocity within 10 km from GNSS stations with the GNSS‐derived velocity where the horizontal component is accurate with a precision of <0.4 mm/yr (Ge et al., 2022; Wei, 2020). We find that east‐west and north‐south velocities from the two methods are consistent within 1‐sigma data uncertainties (Figure S2d in Supporting Information ).…”
Section: Three‐dimensional Velocity Mapsmentioning
confidence: 99%
“…The 3D velocity field from joint inversion is shown in Figure 3 (Ge, 2023; Figures 3a–3c, Figure S2a–S2c in Supporting Information ). We compare the mean velocity within 10 km from GNSS stations with the GNSS‐derived velocity where the horizontal component is accurate with a precision of <0.4 mm/yr (Ge et al., 2022; Wei, 2020). We find that east‐west and north‐south velocities from the two methods are consistent within 1‐sigma data uncertainties (Figure S2d in Supporting Information ).…”
Section: Three‐dimensional Velocity Mapsmentioning
confidence: 99%
“…In a different approach, spatial variations in strain rates have been interpreted to be the result of lateral variations in elastic plate thickness (Chéry, 2008; Traoré et al., 2014) or, more generally, effective lithospheric rigidity (Chéry et al., 2011; Furst et al., 2018). Other studies have focused on constraining rigidity (as well as viscosity) contrasts across major (strike‐slip) faults from an observed asymmetry of elastic strain accumulation with respect to the surface fault trace (e.g., Ge et al., 2022; Houlié & Romanowicz, 2011; W.‐J. Huang & Johnson, 2012; Jolivet et al., 2009; Le Pichon et al., 2005; Schmalzle et al., 2006).…”
Section: Applications Of Secular Velocitiesmentioning
confidence: 99%
“…The total displacement along the Altyn Tagh fault may be over 450 km (Cowgill et al., 2003; Yue et al., 2005). Geometrically, the Altyn Tagh fault is structurally mature with a smooth linear trace, and its present slip rate is ∼10 mm/a along its western‐central segment (Ge et al., 2022; Li et al., 2018; Wang & Shen, 2020). The North Altyn fault is a major splay of the Altyn Tagh fault.…”
Section: Geological Settingmentioning
confidence: 99%
“…(2020) reported that active deformation of the northern Tibetan Plateau has propagated north of the Altyn Tagh (e.g., Sanweishan fault). GPS velocities, historical earthquakes, and fault geomorphic expressions (Figure 1) also reveal that the active deformation is not restricted within the high plateau (Avouac & Peltzer, 1993; Ge et al., 2022; Li et al., 2018; Zheng et al., 2005). Thus, when and how the northward expansion of the Tibetan Plateau occurred remains an enigma.…”
Section: Introductionmentioning
confidence: 99%